2012
DOI: 10.1371/journal.pone.0050131
|View full text |Cite
|
Sign up to set email alerts
|

Early Metabolic Defects in Dexamethasone-Exposed and Undernourished Intrauterine Growth Restricted Rats

Abstract: Poor fetal growth, also known as intrauterine growth restriction (IUGR), is a worldwide health concern. IUGR is commonly associated with both an increased risk in perinatal mortality and a higher prevalence of developing chronic metabolic diseases later in life. Obesity, type 2 diabetes or metabolic syndrome could result from noxious “metabolic programming.” In order to better understand early alterations involved in metabolic programming, we modeled IUGR rat pups through either prenatal exposure to synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 52 publications
6
31
0
4
Order By: Relevance
“…Postnatally, DEX-IUGR pups remained lighter than control animals until weaning (PND21), as previously reported (7). Maternal supplementation with bLf during lactation resulted in different effects compared to the gestational period.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Postnatally, DEX-IUGR pups remained lighter than control animals until weaning (PND21), as previously reported (7). Maternal supplementation with bLf during lactation resulted in different effects compared to the gestational period.…”
Section: Discussionsupporting
confidence: 80%
“…By enhancing fetal lung maturation, this antenatal treatment presents an immediate benefit for preterm neonate survival but long-term consequences of repeated doses of antenatal glucocorticoid include alterations in growth and brain development (6). Rodent studies also showed that antenatal glucocorticoid exposure predisposes the offspring to early glucose intolerance (7) and disturbed cerebral development (8).…”
mentioning
confidence: 99%
“…Consistent with these observations, the prenatally undernourished newborns [22] and weanling pups [24] showed an enhanced adipogenesis (i.e., increased PPARγ and C/EBP isoforms) in the different fat pads before the onset of obesity. In adulthood, the rat offspring from the food-restricted dams also showed an increased expression of the several genes associated with lipogenesis (i.e., FAS and leptin) in a depot-specific manner [22,23].…”
Section: Offspring Of Nutrient-restricted Dams Are Predisposed To Adisupporting
confidence: 74%
“…Numerous studies using maternal nutrition manipulations have revealed a close relationship between altered postnatal leptin surge observed in undernourished rodent (25,26,91,93) or overnourished sheep offspring (74) and fat accumulation in adulthood. Thus, early postnatal leptin blockage leads to longterm leptin resistance and increased susceptibility to diet induced obesity in rats (5), whereas administration of leptin during the postnatal period reverses obesity in prenatally undernourished adult rats (104). Finally, leptin directly activates adipogenesis by promoting differentiation of preadipocytes (13), whereas it shows antilipogenic effects on mature adipocytes (58).…”
Section: Circulating Factorsmentioning
confidence: 99%
“…Numerous studies have described programming effects on the long-term hypothalamus-adipose axis in offspring after maternal excess GC exposure (54). Indeed, prenatal dexamethasone-exposed animals displayed persistent adipogenic gene profiles in a depot-dependent manner (23,33,86,104). Chronic GC exposure activates adipogenesis via both GR and MR primarily by regulating key adipogenic transcription factors (i.e., C/EBP␣, PPAR␥) (22,77).…”
Section: Circulating Factorsmentioning
confidence: 99%